Tetrahydrobiopterin and inherited hyperphenylalaninemias - Blau, Nenad; Thöny, Beat; Spada, Marco; Ponzone, Alberto (The Turkish Journal of Pediatrics, 1996)
Tetrahydrobiopterin deficiency, a variant of hyperphenylalaninemia, may be caused by deficiency of one of the following enzymes: guanosine triphosphate cyclohydrolase 1, 6-pyruvoyltetrahydropterin synthase, dihydropteridin reductase and pterin-4a-carbinolamine dehydratase. The first two enzymes are involved in the biosynthesis of tetrahydrobiopterin, the last two in its regeneration. Although these diseases are rare, early detection by selective screening is essential for the treatment and outcome. Tetrahydrobiopterin deficiencies are very heterogenous ranging from mild forms requiring only marginal if any treatment to severe forms which are in some cases very difficult to treat. All variants of tetrahydrobiopterin deficiency can be differentiated from the classical phenylketonuria (PKU) by measurement of pterin metabolites in patients' urine, tetrahydrobiopterin loading test, and by dihydropteridine reductase activity in erythrocytes from the Guthrie card.
Keywords: hyperphenylalaninemia; phenylketonuria; tetrahydrobiopterin; biopterin; neopterin; phenylalanine; neonatal screening; genetics